Determination of Lead in Cosmetic Sampels Using Coated Wire Lead (II) Ion Selective Electrode Based On Phyropillite - Qonitah Fardiyah; Barlah Rumhayati; Ika Rosemiyani (UPT Penerbitan Universitas Jember, 2016)
A coated wire ion selective electrode (CW-ISE) based on pyrophyllite for detection lead (II) in cosmetic samples was developed. CW-ISE has easy measurement for field analysis, good selectivity and sensitivity. The CW-ISE’s membrane consist of mixture an inorganic material of pyrophyllite as ionophore, polyvinylchloride (PVC) as the matrix polymer, activated carbon and dioktilftalat (DOP) as a plasticizer dissolved in tetrahydrofuran (THF) solvent (1:3 w/v). It showed a good Nernstian slope of 29.33 mV/decade concentration, a lead linear range concentration between 10-1- 10-5 M, and detection limit of 8.054 x10-6 M (equal with 1.669 ppm of lead). And could be used optimally at pH 5 and showed a good selectivity for interfering ions (sodium ion, mercury ion and chromium ion) with selectivity order of lead >mercury>chromium>sodium. The CW-ISE Lead (II) based on pyrophyllite could be applied for determination lead in cosmetic samples, with precision of 95.42% and accuracy of 96.49%. Based on the statistical t test with 5% confidence limit, the potentiometric method and Atomic Absorption Spectrophotometry method had no significant differences.